Circumsubstellar disk SED in dependence on system parameters - Zakhozhay, O. (Advances in Astronomy and Space Physics, 2012)
Formulae for critical angles and areas that permit to imagine configurations of observed systems and to calculate their spectral energy distributions (SEDs) as dependencies on their geometrical parameters and inclination angles toward observer are obtained. Using these formulae an atlas of SEDs was created. The SEDs were calculated for 1120 systems with different central object masses, ages, inner disk radii, flaring geometries and inclination angles. The dependencies of SED shapes on systems ages, inclinations and substellar masses are analysed.